Leadership power in football - Konter, E.; Loughead, T. M.; Paradis, K. F. (Football Psychology - From Theory to Practice, 2019)
The chapter addresses a number of issues related to leadership power in football including conceptual definitions, theoretical approaches, measurement, perceptions, and studies examining leadership power in sport with an emphasis on football. Despite the plethora of research on leadership in sport, an overlooked aspect that forms the nature of leadership is power. There are different sources of power that influence others (e.g. footballers, coaches): expert power, legitimate power, reward power, coercive power, and referent power. Perceptions of power seem to have interactional and dyadic influences that are important in sport (football). In addition, power regulates the nature of the relationship between individuals which has implications for health, fun, development, success, and performance in football. The research would suggest that: (a) football coaches should use the indicated leadership powers for the psychological development of their athletes (e.g. commitment, imagery, peaking under pressure, and coping with stress); (b) coaches` leadership powers have potential to positively influence the team`s dynamics (e.g. cohesion) and performance; (c) expert and referent power yield the most positive associations with psychological skills, and individual and team outcomes; and (d) future research should examine the different types of power perceptions in football in relation to personality types (e.g. Big Five, personality of mood states) and other psychological factors (e.g. self-regulation, self-confidence, motivation, mental toughness, courage) in relation to various environmental factors, cultures, and economic conditions.